Psychoanalytical intervention to babies at risk of autism and other infants’ severe psychopathologies. A supposition of a subject’s clinics - Campanário, Isabela Santoro; Pinto, Jeferson Machado (Clinical Styles. The Journal on the vicissitudes of childhood, 2006)
The author proposed a theoretical and clinical articulation capable of providing support to an earlier psychoanalytical intervention to babies at risk of autism and other severe psychopathologies, as shown by signs of difficulty in establishing mother/child bonds, which could restrict the birth of the subjectivity in the infant. Interdisciplinary professionals that treat autistic children agree that the timing of the beginning of the treatment is essential for accomplishing the best results, which is explained by Medicine because of childrens greater cerebral neuroplasticity. How could psychoanalysis explain such fact, since psychoanalysis time is logical, not chronological?